INCIDENCE AND PREVALENCE OF CHRONIC IRON POISONING AND IT'S MANAGEMENT: A REVIEW - SOUMYA SANTRA,; DIVYA AGRAWAL,; SANJAY KUMAR,; SUDHANSHU SEKHAR MISHRA, (International Journal of Pharma and Bio Sciences, 2014)
Iron, an essential nutrient causes serious diseases in deficient state. But more serious events occur due to the toxicity of iron overload and this leads to morbidity and mortality of a significant population of the world. Chronic iron poisoning can occur due to daily high dietary iron intake, chronic liver disease, rare genetic disorders of iron metabolism, etc. But the commonest causes of severe iron overload are Hereditary Haemochromatosis, Massive ineffective erythropoiesis, secondary iron overload due to frequent repeated red cell transfusion in congenital anaemias (e.g. β-Thlassaemia, Sickle cell anaemia) and Acquired refractory anaemias (e.g. myelodysplasia, aplastic anaemia). In India and South -East Asia, prevalence of Thalassaemia and Sickle cell anemia is indeed alarming. Though, iron poisoning has been a health concern for quite a long period of time, only three drugs could have been developed and put into practice. Even in 2014, not a single agent fulfils the requisites of an ideal iron chelator. Desferrioxamine, Deferiprone and Deferasirox are used as a single drug or in combinations in cases of iron overload diseases and has shown indeed promising results by decreasing the morbidity and adding quality years to life of patients undergoing frequent red cell transfusions. However we still wait for an ideal iron chelator as few drugs are already into phase II clinical trials.